Application of Contextual Teaching and Learning Method to Improve Student Learning Motivation - Audina Melinda (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
Contextual learning which is commonly known as Contextual Teaching and Learning (CTL) is a learning concept that links learning material with the actual (real) conditions at home, school, and community. Students can be expected to think critically in solving problems in learning. In the context of learning this CTL method encourages students to find and explore their own knowledge. So that it can increase students learning motivation because basically the CTL method contains the principle of questioning, with this principle students, are more active as recipients, and there feedback during the learning process. And this is what motivates students to learn because they get their own knowledge.Keywords: Learning Method, Contextual Teaching and Learning, Motivation